2010
DOI: 10.1603/en09190
|View full text |Cite
|
Sign up to set email alerts
|

Floral Transmission ofErwinia tracheiphilaby Cucumber Beetles in a WildCucurbita pepo

Abstract: Cucumber beetles, Acalymma vittatum (F.) and Diabrotica undecipunctata howardi (Barber), are specialist herbivores of cucurbits and the vector of Erwinia tracheiphila (E.F. Smith) Holland, the causative agent of wilt disease. Cucumber beetles transmit E. tracheiphila when infected frass falls onto leaf wounds at the site of beetle feeding. We show that E. tracheiphila also can be transmitted via the floral nectaries of Cucurbita pepo ssp. texana L. Andres (Texas gourd). Under field conditions, we found that be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 35 publications
3
73
0
Order By: Relevance
“…The presence of yeasts and bacteria in floral nectar was recently highlighted [4,23] and it can be deleterious for plants mainly for two reasons: (i) some of these microorganisms can be phytopathogens and also responsible for the infection of plant tissues [24]; (ii) they use nectar as a growing medium altering the content of sugars and amino acids and thus competing with pollinators for this alimentary resource [25]. To counteract the potentially negative impact of nectardwelling microorganisms, plants evolved defense systems that are mainly based on secondary compounds (such as tannins, phenolics and alkaloids) and proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of yeasts and bacteria in floral nectar was recently highlighted [4,23] and it can be deleterious for plants mainly for two reasons: (i) some of these microorganisms can be phytopathogens and also responsible for the infection of plant tissues [24]; (ii) they use nectar as a growing medium altering the content of sugars and amino acids and thus competing with pollinators for this alimentary resource [25]. To counteract the potentially negative impact of nectardwelling microorganisms, plants evolved defense systems that are mainly based on secondary compounds (such as tannins, phenolics and alkaloids) and proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The proliferation of microorganisms depends on their ability to tolerate a wide array of nectar environments that may contain different antimicrobial compounds. Some of these microorganisms are phytopathogens deleterious for plant health that exploit nectarostomata (i.e., the specialized open stomata through which nectar is often released) to enter plant tissues [59,60]. Avoiding proliferation of these microbes in nectar greatly reduces risk of infection.…”
Section: Nectar Dwelling Microorganisms and Their Impact On Pollinatomentioning
confidence: 99%
“…The pathogen gains entry to the inner floral tissues via the nectar secreting stomata, called nectarthodes (Hildebrand and MacDaniels 1935;Rosen 1936;Bubán et al 2003a). The nectary plays an important role also in the transmission of another Erwinia species, E. tracheiphila, which is the causative agent of bacterial wilt disease in cucurbits (Sasu et al 2010a). …”
Section: Hypanthium and Nectarymentioning
confidence: 99%
“…In contrast, Spinelli et al (2007) found that after having reached the nectar cup, E. amylovora moved preferentially inside xylem vessels, although in heavily infected tissues the cortical parenchyma was also colonized. Sasu et al (2010a) also documented the movement of E. tracheiphila through the nectary into the xylem of the pedicel.…”
Section: Hypanthium and Nectarymentioning
confidence: 99%